Awareness and knowledge of diabetic retinopathy in diabetic patients at a General Hospital in Northwest Ethiopia - Getasew Alemu Mersha (SAGE Publishing, 2021)
Objective: Diabetic retinopathy is an evident complication of diabetes on eye and contributes for significant portion of blindness worldwide. In Ethiopia, data are lacking on awareness and knowledge of diabetic retinopathy in diabetic patients. This study desired to assess knowledge of diabetic retinopathy and it is relating factors among diabetic patients attending at a General Hospital in Ethiopia. Methods: We have interviewed 306 diabetic patients who were attending at Debre Tabor General Hospital. Binary logistic regression model was used to recognize associated factors to good knowledge of diabetic retinopathy. Adjusted odds ratio was used to show the power of association. A p -value of less than 0.05 was set to determine its statistical significance. Result: The diabetic patients had a median age of 45 (range = 30) years. From the total diabetic patients, 242 (79.10%) knew that diabetes could affect the eye and 81 (26.50%) were aware of diabetic retinopathy. From those who were informed of diabetic retinopathy, 32 (39.50%) (95% confidence interval = 27.90–51.20) had good knowledge of diabetic retinopathy. High educational status (adjusted odds ratio = 4.08, 95% confidence interval = 1.00–16.50) and non-government employee (adjusted odds ratio = 0.19, 95% confidence interval = 0.05–0.70) were significantly associated with good knowledge of diabetic retinopathy. Physicians and eye doctors were the most frequent source of information for the awareness of diabetic retinopathy. Conclusion: From the total diabetic patients recruited in the study, 39.5% of them obtained information about diabetic retinopathy and the overall knowledge was poor among them. Knowledge of diabetes can affect the eye and it causes blindness was good among majority of the participants. Higher educational status and being a non-government employee were determined to be important predisposing factors of good knowledge. It is also better to involve diabetic educators and counselors in educating diabetic patients on the serious complication of diabetes on eye.